Equity-Advancing Practices at Public Transit Agencies in the United States. Issue 10 (October 2021) - Karner, Alex; Levine, Kaylyn
Consistent with federal anti-discrimination and environmental justice law and guidance, public transportation agencies must evaluate the extent to which their decisions benefit and burden different people and groups and they must also conduct public engagement during decision-making. Assessing benefits and burdens and facilitating engagement are critically important for achieving transportation equity. In practice, quantitative analyses of plan impacts can be used to highlight and mitigate disparate benefits and burdens, but analyses are often conducted after major decisions have already been made and agencies have substantial flexibility in data collection and analysis. Public engagement can also affect equity-related outcomes, but agencies still rely heavily on public meetings and one-way information dissemination approaches that alienate potential participants. Considering the shortcomings associated with quantitative analysis and traditional public engagement as well as the open-ended nature of existing regulatory guidance, there is a need to understand the broad range of approaches that public transit agencies use to pursue equity-related goals. In this review of practice, we summarize six measures that agencies are using to advance transportation equity. Each measure is described using information gleaned from semi-structured interviews and primary source materials. We also identify challenges and shortcomings inherent in each approach using perspectives from the academic literature. The results will be useful for practitioners seeking equitable public transit systems and desiring to go beyond the standard approaches suggested by federal law and guidance.